OP0319 Low and moderate physical activity reduces localised il-1Β in an acute mouse model of gout by down-regulating tlr2 expression on circulating neutrophils. (12th June 2018) - Jablonski, K.; Sandoval, B.; Harb, P.; Kalyanasundaram, A.; Hampton, J.M.; Jarjour, W.N.; Schlesinger, N.; Young, N.A.
Abstract : Background: While physical activity was originally believed to exacerbate inflammation in rheumatic disease, recent studies have shown significant reductions in inflammation with regular exercise. It has been previously shown that down-regulation of toll-like receptor (TLR)2 and TLR4 expression correlates with increased physical activity in humans. Furthermore, both TLR2 and TLR4 knockout mice are resistant to monosodium urate (MSU) crystal-induced gout. Additionally, mesenchymal stem cells (MSCs) can be immunosuppressive by secreting IL-1 receptor antagonist (IL-1RA) and have also been shown to be up-regulated with exercise. Objectives: The aim of this study was to investigate the mechanism by which exercise suppresses gouty inflammation and to define the potential roles of TLR2, TLR4, and MSCs in the process. Methods: NFκB reporter mice [BALB/C-Tg(NFκB-RE-luc)-Xen] were exercised daily by treadmill walking (45 min/day for 2 weeks) at low intensity (35% VO2 max; 8 m/min), moderate intensity (55% VO2 max; 11 m/min), and high intensity (75% VO2 max; 15 m/min). Mice were then injected with MSU crystals (0.5 mg) into the tibio-tarsal joint (ankle). Localised NFκB activity was measured 16 hours later in the injected ankle by bioluminescent imaging. Tissue was collected and processed for immunohistochemical (IHC) analysis and whole blood was collected for both flow cytometry and serum analysis. Results: Mice in the low/moderate intensity exercise groups had decreased inflammation, F4/80 + macrophages, and MPO + neutrophils at the site of MSU injection compared to high intensity and non-exercised controls. Similarly, bioluminescent imaging of NFκB activity was significantly reduced locally in both low/moderate intensity groups compared to high-intensity and non-exercised controls. Surface expression of TLR4 on peripheral monocytes or neutrophils showed little difference by flow cytometry, while TLR2 expression on peripheral neutrophils was significantly reduced. In concordance, localised IL-1β expression via IHC was reduced in low/moderate intensity exercise conditions. IL-1RA expression correlated with IL-1β induction locally by IHC and was elevated in serum. Also, bone marrow-derived MSCs were significantly reduced in low/moderate intensity exercise compared to high-intensity or non-exercised controls. Conclusions: These data show that while low/moderate intensity exercise regimens can reduce the localised MSU crystal-induced inflammation, high intensity training negates this response. Moreover, the exercise-mediated suppression of NFκB activity and IL-1β expression locally can be partially explained by a reduction in peripheral neutrophil recruitment via downregulation of TLR2 expression in the peripheral blood. Although not clearly defined mechanistically in this study, our results also suggest that MSCs may contribute to this immunosuppressive response and are mobilised out of the bone marrow with low/moderate intensity exercise. References: [1] Khanna D, et al. Arthritis Care Res2012;64:1447. [2] Agudelo CA, et al. Arthritis Rheum1972;15:609. [3] Liu-Bryan R, et al. Arthritis Rheum2005;52:2936. Acknowledgements: Support provided by Ironwood Pharmaceuticals, Cambridge MA 02142 Disclosure of Interest: None declared